DINAMIKA PENYELENGGARAAN PELAYANAN PUBLIK DI INDONESIA (Studi Efisiensi, Partisan dan Non Partisan) - Maulidiah, Sri (UIR PRESS, 2016)
Public service is a basic function of his government, because the government has historically existed and was held to meet the interests and needs of the community or its members. Public service is a public bureaucracy product received by the citizens of users and society at large. Therefore, the public service can be defined as a series of activities undertaken by the bureaucracy of public institutions to meet the needs and interests of the various forms of citizen users. Government essentially has the basic functions of the service in accordance with the history of the formation of state / government of the state concept sebgai night watchman, therefore the government is obliged to serve their communities in an effort to meet the various needs of the community, especially the basic human needs such as security, a sense of ease, and etc. Unlike the wide range of products services in the form of goods easily in the value of quality, in terms of products services in the form of services which are not easy for the value of quality. Nevertheless, the ministry of goods and services often are complementary or complementary to each other so it is difficult to be separated from each other. A product in the form of goods is often accompanied by the services, such as car sales effort along with services such as warranty and service. Likewise, services are also often accompanied by the ministry of goods. For example, electrical installation services would be accompanied by the installation of power poles and other supporting equipment. Intangible goods services so it does not appear (intangible). Although its form does not appear, but in the process of implementation can or can to be observed and felt, for example, a service can be judged walk fast, slow, unpleasant, difficult, expensive, or expensive in terms of costs.